On the structure of skew groupoid rings which are Azumaya - Flores, D.; Paques, A. (Algebra and Discrete Mathematics, 2013)
In this paper we present an intrinsic description of the structure of an Azumaya skew groupoid ring, having its center contained in the respective ground ring, in terms of suitable central Galois algebras and commutative Galois extensions.